FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PENYEMBUHAN LUKA POST OP SEKSIO SESARIA DI RSUD BANGKINANG - Devina Yuristin (Universitas Pahlawan, 2018)
The process of wound healing involves the integration of physiological processes. The healing properties of all wounds are the same, with variations depending on the location, severity and extent of the injury. The ability of tissue cells to regenerate or return to normal structures through cell growth also affects wound healing. There are several factors that influence the wound healing process, namely; addition of age, nutritional status and infection. The purpose of this study was to determine the factors associated with post-op cesarean section wound healing in Bangkinang Hospital in 2018. The study design was cross sectional. The population in this study were all postoperative cesarean section patients in Bangkinang Hospital at the time of the study, with a sample of 31 people. The sampling technique is accidental sampling. The measuring instruments used are observation sheets and checklist sheets. Data collection uses primary data and data processing using computerization which includes editing, coding, data entry and cleaning. Analysis of the data used is univariate and bivariate with the fisher's exact test. The results showed that a significant relationship between age, nutritional status, post-cesarean section postoperative wound healing in Selasih District Hospital Pelalawan District was shown in each variable by p value <0.05. It is expected that health workers can provide information about factors related to post-op cesarean section wound healing. In addition, it is also expected to the Bangkinang Regional Hospital to provide training to officers in handling post-op cesarean section injuries.